2013
DOI: 10.1159/000343762
|View full text |Cite
|
Sign up to set email alerts
|

Novel Anti-Inflammatory Effects of Doxazosin in Rodent Models of Inflammation

Abstract: Background: Doxazosin is an α1-adrenergic receptor antagonist for the treatment of high blood pressure and benign prostatic hyperplasia. Peripheral α-adrenergic receptors have been implicated in inflammation. Aim: To examine the anti-inflammatory effects of doxazosin in rodent models of inflammation. Method: The anti-inflammatory properties of doxazosin were investigated in 4 models. In all studies, drug treatment was administered 15 min prior to challenge. In the lipopolysaccharide (LPS)-induced sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…6–8-week old mice were randomly divided into four groups. 0.25 mg/kg body weight (BW) of LPS was selected to induce inflammation according to previous studies [18], [19]. In saline and LPS-treated groups, mice were injected intraperitoneally with 100 µL of saline and 0.25 mg/kg LPS in 100 µL of saline.…”
Section: Methodsmentioning
confidence: 99%
“…6–8-week old mice were randomly divided into four groups. 0.25 mg/kg body weight (BW) of LPS was selected to induce inflammation according to previous studies [18], [19]. In saline and LPS-treated groups, mice were injected intraperitoneally with 100 µL of saline and 0.25 mg/kg LPS in 100 µL of saline.…”
Section: Methodsmentioning
confidence: 99%
“…Several proinflammatory cytokines, including CCL2, IL‐1β and TNF‐α, were induced in the subretinal fluid obtained from human eyes with RD (unpublished observations of the authors) and have previously been reported to contribute to the pathogenesis of photoreceptor death after RD (Nakazawa et al ., ; Nakazawa et al ., ; Kataoka et al ., ). Moreover, different types of ARs have been shown to be implicated in inflammatory responses within various injury models (Tung et al ., ; Way et al ., ). Thus, we next evaluated the roles of α 1 ‐ and α 2 ‐adrenoceptors in the RD‐induced up‐regulation of proinflammatory cytokines.…”
Section: Resultsmentioning
confidence: 99%
“…For all these treatments, the vehicle was 20% DMSO. The doses of the drugs were based on previous studies (Haruta et al, 2009;Yanpallewar et al, 2010;O'Neil et al, 2013;Tung et al, 2013;Way et al, 2015;Zhang et al, 2015).…”
Section: Drug Administrationmentioning
confidence: 99%
“…mediators [49,50] and pain [21], and subtype-selective a 1 -AR antagonists inhibit uncomfortable symptoms in patients with benign prostatic hyperplasia [51]. Thus, the effects of applying these agents after acute burns should be further explored.…”
Section: Discussionmentioning
confidence: 99%